Sources of Hieronymus Bosch: Literary and Pictorial Influences on The Extraction of the Stone of Madness - Oromendía de la Fuente, Enrique (Eikón / Imago, 2019)
This article deals with the interpretation of The Extraction of the Stone of Madness by analyzing the influence exerted by Das Narrenschiff, by Sebastián Brant, Malleus Maleficarum, by Heinrich Kramer and Jakob Sprenger, De imitatione Christi, by Thomas von Kempen and Le Miroir des âmes simples, by Marguerite Porete in the genesis of the painting. As a result of this analysis, it has been possible to give a coherent explanation of the meaning of the inscription that surrounds the painting, an identification of the people that make up the scene has been suggested, the type of flowers that appear in the painting has been unraveled, the object that the patient carries in his bag has been clarified as well as the meaning of the doctor’s funnel and symbolic interpretations of some characters are provided. All these things change the vision that has been taken of the picture until this moment.